Pancreatoscopy-Directed Electrohydraulic Lithotripsy for Pancreatic Ductal Stones in Painful Chronic Pancreatitis Using SpyGlass. Issue 4 (April 2017) - Bekkali, Noor L.H.; Murray, Sam; Johnson, Gavin J.; Bandula, Steven; Amin, Zahir; Chapman, Michael H.; Pereira, Stephen P.; Webster, George J.M.
Abstract : Objective: Painful chronic pancreatitis is often associated with main duct obstruction due to stones. Approaches to management are challenging, including surgery, extracorporeal shock wave lithotripsy, or endoscopic approaches. Here, we report our experience of pancreatoscopy + electrohydraulic lithotripsy (EHL) for pancreatic duct (PD) stones using SpyGlass. Methods: We retrospectively audited the use of SpyGlass (Legacy and DS) + EHL. Indication, procedural details, and clinical outcomes were assessed. Results: A total of 118 SpyGlass + EHL procedures for stones were performed, of which 8 (7%) for pancreatic stones, in 6 patients (3 female; mean [standard deviation] age, 45 [7] years). All patients had painful chronic pancreatitis, with radiological evidence of a dilated PD, and main duct stone disease. Surgical options had been considered in all cases. Stone fragmentation and PD decompression were achieved in 83% (n = 5) without complications. Two patients required 2 EHL procedures to achieve clearance. In 1 patient with failed clearance, pancreatoscopy revealed a stone in the adjacent parenchyma and not in PD. All patients with successful EHL had pain relief/marked improvement at clinical review (mean [standard deviation] follow-up, 2.7 [1.1] years). Conclusions: Pancreatoscopy + EHL may have a valuable role in treating obstructing PD stones, possibly avoiding the need for surgery in some patients. Abstract : Supplemental digital content is available in the text.